ICF-guided home-based physiotherapy interventions – assessing their impact on quality of life in palliative care for patients with rheumatoid arthritis: a pilot study - Raheem Khan, Abdur; Khan, Ashfaque; Aafreen; Kumar Maurya, Neeraj; Ahmad, Ausaf; Fauzan Akhtar, Syed M.; Abu Shaphe, Mohammad; Ahmed, Hashim (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. The current study assessed the impact of the International Classiﬁcation of Functioning, Disability and Health (ICF)-guided home-based physiotherapy programs on improving quality of life in patients with rheumatoid arthritis (RA) receiving palliative care.Methods. The study used a two-arm parallel group pretest-posttest experimental group design. A total of 50 RA patients re-ceiving palliative home care were recruited based on the eligibility criteria and randomly allocated to an intervention group (n = 25) that received ICF-guided physiotherapy with standard care or a control group (n = 25) that received only standard care. The study used the Short Form Health Survey (SF-36) to assess quality of life, the Health Assessment Questionnaire (HAQ) to measure physical function, the Visual Analogue Scale (VAS) to determine pain levels, and the Hospital Anxiety and Depression Scale (HADS) to evaluate psychological health. Data was collected at the start of the study and after a 12-week intervention period.Results. The intervention group had signiﬁcant improvements for all outcome scores, including SF-36 (p < 0.001), HAQ (p < 0.001), and VAS (p < 0.001) when compared to the control group.Conclusions. The ﬁndings emphasise the considerable potential of ICF-guided home-based physiotherapy interventions in enhancing the quality of life, physical functionality, pain management, and psychological health of RA patients receiving palliative care. Implementing such interventions as part of the palliative care protocol for RA patients could greatly improve patient out-comes. However, additional long-term studies are advised to conﬁrm these beneﬁts and reﬁne the intervention strategies.
Keywords: palliative care; quality of life; physiotherapy; International Classiﬁcation of Functioning, Disability and Health (ICF); pain management; physical functioning; psychological well-bein